2009
DOI: 10.1186/cc7901
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of renal replacement therapy in acute kidney injury: perspective from within the Acute Renal Failure Trial Network Study

Abstract: Determination of the optimal dose of renal replacement therapy in critically ill patients with acute kidney injury has been controversial. Questions have recently been raised regarding the design and execution of the US Department of Veterans Affairs/National Institutes of Health Acute Renal Failure Trial Network (ATN) Study, which demonstrated no improvement in 60-day all-cause mortality with more intensive management of renal replacement therapy. In the present article we present our rationale for these aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…Another pitfall is the choice of in-hospital mortality as the primary outcome; hospital or long-term care facility transfer practices and short follow-up times may underestimate the strength of the association with mortality (19). These limitations may be particularly relevant in patients with AKI, where RRT and/or recovery span over weeks rather than days (2). Moreover, patients with severe illness typically have an eventful ICU course, where the relation between a risk factor determined at baseline and outcome is likely to be nonlinear, may change over time, and/or reverse direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another pitfall is the choice of in-hospital mortality as the primary outcome; hospital or long-term care facility transfer practices and short follow-up times may underestimate the strength of the association with mortality (19). These limitations may be particularly relevant in patients with AKI, where RRT and/or recovery span over weeks rather than days (2). Moreover, patients with severe illness typically have an eventful ICU course, where the relation between a risk factor determined at baseline and outcome is likely to be nonlinear, may change over time, and/or reverse direction.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) requiring dialysis occurs in 1% to 4% of hospitalized patients and, in the setting of multisystem organ failure, is associated with exceptionally high morbidity and mortality (1)(2)(3). To date, there is no specific treatment for AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that, in these patients, out of >200 circuit starts only less than 1 in 12 experienced significant hypotension, suggests that the approach we describe provides a reasonable initial step toward protection. Some direct comparison can be made with a report from the ATN trial performed in the United States [13] despite any specific information on how CRRT was started in that trial. In their ATN report, Palevsky et al [13] found that 20.8% of patients receiving CRRT needed to have an escalation in vasopressor therapy sufficient to increase their SOFA CVS score.…”
Section: Discussionmentioning
confidence: 99%
“…Some direct comparison can be made with a report from the ATN trial performed in the United States [13] despite any specific information on how CRRT was started in that trial. In their ATN report, Palevsky et al [13] found that 20.8% of patients receiving CRRT needed to have an escalation in vasopressor therapy sufficient to increase their SOFA CVS score. In our study, 19.2% of patients experienced a similar change.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because of some important shortcomings of the ATN trial [18], an expert panel from the SRLF in France [17] (not necessarily the strongest advocates of the 35-ml/kg/h dose) felt obliged to recommend the continued use of the 35 ml/kg/h dose in to treat septic AKI in ICU patients thereby softening somewhat the message of the ‘RENAL’ (Randomised Evaluation of Normal vs. Augmented Level of Replacement Therapy) study which was not designed for the evaluation of septic AKI [19]. On the other hand, Palevsky et al [20] recently turned down the idea that their study supported an approach of therapeutic nihilism, as suggested by Ronco et al [18]. They argued that a less intensive strategy might provide a level of renal support that often exceeds routine clinical practice and suggested to put greater emphasis on ensuring the actual delivery of an appropriate prescribed dose of therapy.…”
Section: Importance Of Renal Replacement Therapy Type Dosing and Timmentioning
confidence: 99%